BRIDGING CULTURES THROUGH HONEY: ETHICAL INTEGRATION OF TRADITIONAL WISDOM AND MODERN SPORTS NUTRITION IN WEST SUMATRA - Rahmad, Hari Adi; Azri, Harizqi; Yuhendri, Rival; Rahmat, Wahyudi; Fitriyah, Rifkah (LLDIKTI Wilayah X, 2025)
This study addresses the growing disconnection between scientific health promotion and traditional cultural practices in multicultural societies. In Indonesia, particularly in West Sumatra, indigenous health knowledge rooted in Minangkabau philosophy has long emphasized balance, respect, and communal well-being. However, in the context of globalized sports nutrition and cross-cultural communication, these values are often marginalized or misinterpreted. The challenge lies in integrating ethical communication with traditional health practices, such as the consumption of stingless bee honey (Galo-galo), into modern health and sports systems without reducing them to mere commodities. The research aims to explore the intersection of cross-cultural communication ethics, multicultural values, and sports nutrition by examining the functional role of West Sumatra honey as both a nutritional and cultural medium. Using a qualitative descriptive approach, the study analyzes how Minangkabau health traditions can be ethically conveyed in pluralistic contexts to promote athlete performance and public well-being. Laboratory findings indicate that West Sumatra stingless bee honey exhibits superior phytochemical properties, with total phenolic content ranging from 39.98 to 81.02 mg GAE/g and α-glucosidase inhibition of 67.6%, confirming its strong antioxidant and anti-hyperglycemic potential. In applied sports contexts, supplementation with Galo-galo honey correlates with stable blood glucose levels and faster heart rate recovery (HRR) in rowing and soccer athletes. By integrating Minangkabau philosophical ethics, such as duduk samo randah and tagak samo tinggi, the study proposes a model of ethical communication grounded in empathy and cultural humility. The results underscore that fostering cross-cultural communication ethics through traditional resources not only enhances physical performance and health but also strengthens social harmony and cultural resilience in an increasingly globalized era.